Research on Data Confidentiality and Security Protocol in Computer Network. Issue 3 (October 2020) - Li, Yizhi
Abstract: With the development of society, we are going the Information age. With the Internet, we can improve our work efficiency and management level. Because of the Internet, we can chat with others in a new way. However, because of the particularity in the internet, our computer internet meets too many problems, for example, when we surfing the Internet, user privacy was leaked and the transaction process was peeped. So we need to solve these problems, and the best way to solve these problems is to understand these problems clearly. So to get this target, the article tells the concept of computer network firstly, and then writes the problems in Computer Network Security. On the other hand, the article analyzes the computer network information security and security all. After these things, we will make our Internet better and better.